TINJAUAN YURIDIS WEDDING ORGANIZER DALAM MELAKUKAN PERIKLANAN PERNIKAHAN ANAK DIBAWAH UMUR MELALUI MEDIA ONLINE - Kartina Pakpahan; Heriyanti Heriyanti; Nadya Khairani (Legal Standing : Jurnal Ilmu Hukum, 2023)
The spread of promotional materials in the modern world is greatly helped by advances in technology. The wedding ran smoothly because of the actions of many people and groups, such as the wedding organizer (WO). This study aims to explain the regulation of criminal acts and criminal liability for WO business actors who advertise underage marriages through social media and websites, as well as possible criminal penalties and sanctions that can be used against those who are responsible for advertising violations. This investigation is based on methods for analyzing descriptive-analytic studies, legal-normative analysis, and qualitative data. This legal writing is largely about studying a statewide collection of literature, data, and documentation for legal instruments. The results of the discussion explained that companies that encourage underage marriages violate Article 59(2)(d) of Law No. 35 of 2014 concerning Child Protection. Law Number 16 of 2019 concerning Marriage Article 7 Paragraph 1 states that underage child marriage is invalid. This is because it is against the law because you have to be 18 years old to get married. Article 8 paragraph 1 letter an of Law Number 8 of 1999 concerning Consumer Protection states that WO business actors advertising underage child marriages is against the law. As stated in the first sentence of article 27 of Law Number 19 of 2016 concerning ITE, it is a crime to advertise in a way that is against the law and is not in accordance with statutory regulations. When the subjective and objective requirements of Article 20 jo. Article 60 paragraphs (1) and (2) of Law No. 8 of 1999 concerning Consumer Protection and Article 45 paragraph (1) of Law No. 19 of 2016 concerning Information and Electronic Transactions are fulfilled, the perpetrators can be held accountable for their actions.